Structural behavior of shear deficient high performance reinforced concrete exterior joints under bending. (February 2023) - Yeganeh, A.E.; Hossain, K.M.A.
Abstract: Structural performance of shear deficient reinforced concrete exterior beam-column connections made with Engineered Cementitious Composite (ECC) and Ultra-high Performance Concrete (UHPC) is investigated experimentally and compared with those made of Self-Consolidating Concrete (SCC). Beam-column connections of 1/3rd scale made entirely of ECC, SCC and UHPC as well as ECC-SCC and UHPC-SCC combinations (joint core zone made of ECC and UHPC while the rest made with SCC) are tested under monotonic flexural loading to failure. The performance is compared in terms of failure mode, ductility, energy absorption capacity, stiffness, load/moment-displacement/rotation response, stress–strain characteristics, crack patterns/widths, member flexural/shear strength and joint shear strength. SCC and SCC-UHPC joint specimens have non-ductile beam shear failure and shear failure of the SCC part of the connection respectively, while all others have joint flexural failure. Code based equations significantly under predicted the shear strength of ECC and UHPC joint members. All connections made fully or partially with UHPC and ECC have exhibited higher ductility (1.2 to 1.7 times), energy absorption capacity (3.1 to 15.7 times) and reserve joint strength compared to those with SCC. UHPC incorporated connections exhibited higher strength and energy absorbing capacity, those with ECC showed higher ductility and better crack control characteristics and incorporation of ECC/UHPC can induce desired flexure dominated failure in a shear deficient joint.